Plan de negocio del producto palim para su posicionamiento en el mercado de la provincia de Manabí - Avellán Ganchozo, Lizeth Alejandra (2017)
The research aimed at structuring a business plan for the positioning of the PALIM product (lemon juice and panela) in the market of the Province of Manabí, determining the market, technical, economic and financial feasibility. In stage I, a market study was carried out in the cantons of Portoviejo, Jipijapa, Manta, Chone and Bolívar, through surveys of a sample of the economically active population, corresponding to 384 people; Obtaining data that allowed to identify low levels of consumption; That is, 25% purchase this beverage, while 75% do not, an unsatisfied demand of 92%, with a monthly production requirement of 21,000 units. In phase II, a technical analysis was developed, where the characteristics of the facilities were detected in terms of plant size, installed capacity, location, organizational structure and distribution of functions. Regarding the economic-financial study (stage III), an investment of $ 210,315.35 was established, with annual revenues of $ 223,200.00, the unit product cost of 0.58 cts. Of the 500ml bottles, reaching the market at 0.70 ctv. In conclusion, financial indicators with positive results showed that the project is fully profitable and viable, as the value of the IRR is set at 27.32%, exceeding the discount rate (16%), the estimated investment recovery period In 3 years and estimated a consumption rate of 833,384.74 people would be willing to purchase the PALIM juice, demonstrating feasibility of investment and position the drink in the province.